2021
DOI: 10.3389/fonc.2021.651693
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MIAT/HMGB1 Axis Is Involved in Cisplatin Resistance via Regulating IL6-Mediated Activation of the JAK2/STAT3 Pathway in Nasopharyngeal Carcinoma

Abstract: Cisplatin-based chemotherapy and radiotherapy are the main first-line treatment strategies for nasopharyngeal carcinoma (NPC) patients. Unfortunately, resistance is a major obstacle in the clinical management of NPC patients. We prove that the expression level of high-mobility group box 1 (HMGB1) is dramatically increased in resistant NPC cells than that in sensitive cells. HMGB1 induces the expression and secretion of IL6, which leads to constitutive autocrine activation of the JAK2/STAT3 pathway and eventual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Previous work has identified the JAK2/STAT3 pathway to be involved in cisplatin resistance of nasopharyngeal carcinoma [ 16 ] and epirubicin resistance of NSCLCs [ 17 ]. It was also reported that the phosphorylation levels of JAK2 and STAT3 were significantly elevated in cisplatin-resistant NSCLC cell lines compared with those in cisplatin-sensitive NSCLC cell lines [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has identified the JAK2/STAT3 pathway to be involved in cisplatin resistance of nasopharyngeal carcinoma [ 16 ] and epirubicin resistance of NSCLCs [ 17 ]. It was also reported that the phosphorylation levels of JAK2 and STAT3 were significantly elevated in cisplatin-resistant NSCLC cell lines compared with those in cisplatin-sensitive NSCLC cell lines [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The JAK2/STAT3 pathway has been considered a promising target for chemotherapeutic interference ascribed to its persistent activation in human carcinomas [ 14 ]. This pathway is also found to be involved in drug resistance in diverse cancers, such as gemcitabine resistance in pancreatic cancer [ 15 ], cisplatin resistance in nasopharyngeal carcinoma [ 16 ], and epirubicin resistance in NSCLCs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lncRNA MIAT can be used as a target, and inhibition of lncRNA MIAT expression can reverse chemoresistance in nasopharyngeal carcinoma to some extent. 98 The authors found that lnc NEAT1 interacted with let-7a-5p, and the two were negatively correlated. Let-7a-5p inhibited chemoresistance and improved chemosensitivity in nasopharyngeal carcinoma.…”
Section: Non-coding Rnas Involved In Drug Resistance Of Npcmentioning
confidence: 99%
“…Zhu et al proved that lncRNAs MIAT and HMGB1 are upregulated in cisplatin-resistant nasopharyngeal carcinoma cells, are biological targets that promote cisplatin resistance, and can initiate the JAK2/STAT3 pathway by promoting the expression level of self-IL6, further increasing cisplatin resistance in nasopharyngeal carcinoma cells. 98 Moreover, Ras-MAPK is an important intracellular signalling pathway that regulates apoptosis, the cell cycle and many other cellular processes. Low expression of NEAT1 inhibited the expression level of let-7a-5p, which reduced the activity of the Ras-MAPK signalling pathway and increased the sensitivity of NPC cells to cisplatin.…”
Section: Non-coding Rnas Involved In Drug Resistance Of Npcmentioning
confidence: 99%
“…More recently, many other lncRNAs have been associated with NPC progression, with their capacity of sponging different microRNAs [ 58 , 61 , 62 , 63 , 71 , 72 , 73 , 74 ]. Additionally, in NPC patients, a large number of lncRNAs were also associated with cisplatin resistance [ 42 , 43 , 44 , 45 , 75 , 76 , 77 , 78 ] and radioresistance [ 54 , 79 , 80 ].…”
Section: Lncrnas In Rare Tumorsmentioning
confidence: 99%